PENINGKATAN HASIL BELAJAR KOGNITIF MATA PELAJARAN EKONOMI PADA MATERI LEMBAGA JASA KEUANGAN DENGAN PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN LURING PADA SISWA KELAS X IS DI SMA NEGERI 1 TANJUNGBALAI TAHUN PELAJARAN 2023/2024 - Fitri Lindasari (JIP: Jurnal Ilmu Pendidikan, 2024)
This research aims to determine the magnitude of the increase in student learning activity through the application of the Problem Based Learning learning model in economics subjects. This research is Classroom Action Research (PTK) carried out by economics subject teachers. The research was carried out in two cycles. Each cycle consists of planning stages, implementing actions, observing and reflecting. The subjects of this research were 35 students of class X IS SMAN 1 Tanjungbalai. Data collection techniques use tests. The results of research using the Problem Based Learning model from cycle I to cycle II: student cognitive learning outcomes increased by 31%.